q-Difference equations for the 2-iterated q-Appell and mixed type q-Appell polynomials - H. M. Srivastava (Arabian Journal of Mathematics, 2018)
Abstract In this article, the authors establish the recurrence relations and q-difference equations for the 2-iterated q-Appell polynomials. The recurrence relations and the q-difference equations for the 2-iterated q-Bernoulli polynomials, the q-Euler polynomials and the q-Genocchi polynomials are also derived. An analogous study of certain mixed type q-special polynomials is also presented.